Market Liquidity and Trading Activity - Chordia, Tarun; Roll, Richard; Subrahmanyam, Avanidhar (Journal of Finance, 2001)
ABSTRACT Previous studies of liquidity span short time periods and focus on the individual security. In contrast, we study aggregate market spreads, depths, and trading activity for U.S. equities over an extended time sample. Daily changes in market averages of liquidity and trading activity are highly volatile and negatively serially dependent. Liquidity plummets significantly in down markets. Recent market volatility induces a decrease in trading activity and spreads. There are strong day‐of‐the‐week effects; Fridays accompany a significant decrease in trading activity and liquidity, while Tuesdays display the opposite pattern. Long‐ and short‐term interest rates influence liquidity. Depth and trading activity increase just prior to major macroeconomic announcements.